PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2011) - Kusuma Wardani, Nurul; Januarti, Indira (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the effect of firm characteristics on the disclosure of corporate social responsibility. Disclosure of corporate social responsibility is the dependent variable in this study as measured by Key Success Factors are based on the Performance of Social containing 78 indiktor measuring corporate social responsibility. The independent variables were studied. commissioners size, profitability, and leverage. The independent variables were studied Commissioners size, profitability,and leverage.The sample is a manufacturing company listed on the Indonesia Stock Exchange in the year 2009 to 2011. The sample is a manufacturing company listed on the Indonesia Stock Exchange in the year 2009 to 2011. The sample was selected using purposive sampling method and obtained a sample of 140 companies. Analysis data was performed with the classical assumption test and hypothesis testing multiple regression analysis. Analysis data was performed with the classical hypothesis testing Assumption test and linear regression method.The results of this study indicate that the variable size of the board of commissioners and a significant positive effect on the profitability of corporate social responsibility disclosure. The results of this study indicate that the variable size of the board of Commissioners and a significant positive effect on the profitability of corporate social responsibility disclosure. While significant negative leverage variable on the disclosure of corporate social responsibility. While significant negative leverage variable on the disclosure of corporate social responsibility.